The complete mitochondrial genome of big-eye mandarin fish Siniperca kneri (perciformes: Sinipercidae) from Hanjiang river. Issue 1 (2nd January 2019) - Chen, Suwei; Tang, Qiongying
Abstract: Siniperca kneri is endemic to East Asia with important economic values, and its natural resource is decreasing dramatically. In this study, the complete mitogenome sequence of S. kneri from Hanjiang River was determined using next-generation sequencing. The mitogenome is 16, 496 bp in length, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 non-coding control region. The phylogenetic analyses based on whole mitogenome sequences indicated that S. kneri individuals did not form a monophyly, having a close relationship with Siniperca chuatsi . The present result will provide basic data for the genetic diversity conservation of S. kneri .